Frugivorous bird characteristic of seed disperser in shrubland tropical forest West Java, Indonesia - RUHYAT PARTASASMITA; ANI MARDIASTUTI; DEDY DURYADI SOLIHIN; REVIANY WIDJAJAKUSUMAH; SITI NURAMALIATI PRIJONO (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Partasasmita R, Mardiastuti A, Solihin DD, Widjajakusumah R, Prijono SN. 2016. Frugivorous bird characteristic of seed disperser in shrubland tropical forest. Biodiversitas 18: 263-268. Java has been experiencing a heavy deforestation in the 16th century. Combined with a densely human population, most forests have changed into open land with shrubs and secondary vegetation. For examples Bulbul, flowerpecker and White-eye are three large groups of frugivorous birds and has been known as an effective seed dispersal agent and fostering vegetation recovery. However, variations in the use of fruit by fruit-eating birds very closely linked to the characteristic morphology and feeding behavior. The proportion of fruit in the diet probably varies widely between species, but, for all the best-studied species, fruit it at last seasonally dominant. It is highly frugivorous, particularly in wet season, and consumes the full range of fruit types within it’s gave limit, defecating (or, sometimes regurgitating) all seeds intact. According to the some reference that fruit consumers such as Bulbuls, Flowerpeckers, and White-eyes are some time is called seed dispersal. But there is no information on seed fate. So, this paper describes the frugivorous bird characteristic of seed disperser shrubland tropical forest at Panaruban, Subang. West Java, Indonesia. Observation of frugivorous bird’s communities was used by capture-recapture method. The frugivorous bird morphology characteristic was measured which consisted of external morphology and digest system morphology. The result shown that frugivorous birds had gape width-height ratio of ≥ 0.90. Frugivorous bird thin-walled gizzard relationship with gizzard weight to determine safety of seed exit with feces in a state of is intact. There was strong interaction between frugivorous bird-fruit by gape width-height and fruit diameter. Keywords: Frugivorous birds, seed dispersal, guild, Panaruban